Enhancing Organizational Ambidexterity in SMEs. The Critical Role of Digital Technologies - Marchetti, Riccardo (My University, 2025)
Nowadays, small and medium enterprises (SMEs) are under increasing pressure to adapt, innovate, and maintain their competitiveness. Digital technologies, such as Artificial Intel-ligence (AI), Internet of Things (IoT), Cloud Computing, and Big Data, have become essen-tial tools for achieving Organizational Ambidexterity (OA), which refers to the ability to balance innovation (exploration) with operational efficiency (exploitation). This study investigates how digital technologies support Organizational Ambidexterity in SMEs exploring the relationships between technology adoption, strategic alignment, and organizational transformation.Using a robust theoretical framework that integrates the concepts of OA, the Technology-Organization-Environment (TOE) model, and leadership practices, this research employs a qualitative case study approach. Semi-structured inter-views with Italian SMEs across both technological and traditional industries offer deep insights into the factors influencing technology adoption and the methods used to balance innovation with efficient operations. The findings indicate that digital technologies play a critical role in enabling OA, yet SMEs encounter challenges such as limited resources, resistance to change, and an underdevel-oped digital culture. Enabling factors include the presence of dedicated innovation teams, adaptable leadership styles, strategic collaborations, and technologies designed to align with workforce skills. Additionally, fostering a culture of learning and collaboration is cru-cial to bridging technological gaps and overcoming organizational inertia.From a manageri-al standpoint, this study underscores the importance of aligning technology adoption with long-term business objectives, continuously developing employee skills, and implement-ing agile frameworks to maintain adaptability and responsiveness. Managers should priori-tize investment in scalable and impactful digital solutions while embracing iterative eval-uation processes to optimize outcomes. This study adds to the literature on Organizational Ambidexterity (OA) and digital transformation by illustrating how SMEs can harness emerg-ing technologies to succeed in rapidly changing environments. Future research should inspect deeper into leadership styles that promote OA, examine the perspectives of em-ployees on digital innovation and digital technologies, and pursue cross-country compari-sons to improve the broader applicability of these findings.
Keywords: innovations; digital technology; small and medium-sized enterprises; digitalisation; artificial intelligence; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development